Dynamics of long-distance signaling via plant vascular tissues - Notaguchi, Michitaka; Okamoto, Satoru (Frontiers in Plant Science, 2015)
Plant vascular systems are constructed by specific cell wall modifications through which cells are highly specialized to make conduits for water and nutrients. Xylem vessels are formed by thickened cell walls that remain after programmed cell death, and serve as water conduits from the root to the shoot. In contrast, phloem tissues consist of a complex of living cells, including sieve tube elements and their neighboring companion cells, and translocate photosynthetic assimilates from mature leaves to developing young tissues. Intensive studies on the content of vascular flow fluids have unveiled that plant vascular tissues transport various types of gene product, and the transport of some provides the molecular basis for the long-distance communications. Analysis of xylem sap has demonstrated the presence of proteins in the xylem transpiration stream. Recent studies have revealed that CLE and CEP peptides secreted in the roots are transported to above ground via the xylem in response to plant-microbe interaction and soil nitrogen starvation, respectively. Their leucine-rich repeat transmembrane receptors localized in the shoot phloem are required for relaying the signal from the shoot to the root. These findings well fit to the current scenario of root-to-shoot-to-root feedback signaling, where peptide transport achieves the root-to-shoot signaling, the first half of the signaling process. Meanwhile, it is now well evidenced that proteins and a range of RNAs are transported via the phloem translocation system, and some of those can exert their physiological functions at their destinations, including roots. Thus, plant vascular systems may serve not only as conduits for the translocation of essential substances but also as long-distance communication pathways that allow plants to adapt to changes in internal and external environments at the whole plant level.